License to Regulate: Noncoding RNA Special Agents in Plant Meiosis and Reproduction - Dziegielewski, Wojciech; Ziolkowski, Piotr A. (Frontiers in Plant Science, 2021)
The complexity of the subcellular processes that take place during meiosis requires a significant remodeling of cellular metabolism and dynamic changes in the organization of chromosomes and the cytoskeleton. Recently investigations of meiotic transcriptomes have revealed additional non-coding RNA factors (ncRNAs) that directly or indirectly influence the course of meiosis. Plant meiosis is the point at which almost all known non-coding RNA-dependent regulatory pathways meet to influence diverse processes related to cell functioning and division. ncRNAs have been shown to prevent transposon reactivation, create germline-specific DNA methylation patterns and affect the expression of meiosis-specific genes. They can also influence chromosome-level processes, including the stimulation of chromosome condensation, the definition of centromeric chromatin, and perhaps even the regulation of meiotic recombination. In many cases, our understanding of the mechanisms underlying these processes remains limited. In this review, we will examine how the different functions of each type of ncRNA have been adopted in plants, devoting attention both to well-studied examples and to other possible functions about which we can only speculate for now. We will also briefly discuss the most important challenges in the investigation of ncRNAs in plant meiosis.